Faculty training for web enhanced learning - Repetto, Manuela; Trentin, Guglielmo (Education in a competitive and globalizing world series., 2011)
Faculty training as a key factor for web enhanced learning sustainability / Guglielmo Trentin and Serena Alvino -- A framework to investigate adoption of computer supported collaborative learning by teachers at university / Stefano Renzi and Jane Klobas -- Five reasons for the recluctance of academic faculty to employ a web-enhanced learning / Sarah Guri-Rosenblit -- Teacher resistance to new technologies: how barriers to web enhanced learning can be overcome / Steve Wheeler -- Promoting WELlin university teaching: current practice in web-enhanced faculty development / Gail Wilson -- Beginning to begin / Kim Floyd [and others] -- Changing technologies/renewing pedagogies: implications for university teaching and learning / Karen Starr, Elizabeth Stacey and Lauri Grace -- Ecompetence to move faculty towards a sustainable use of learning technologies in higher education / Dirk Schneckenberg -- Pedagogy of the Web: improving practice teaching and learning online / David Whittier -- From pedagogical research to embedded e-learning / Harvey Mellar and Magdalena Jara -- Cultural impact on online education: how to develop self-awareness in online teachers / Manuela Milani -- Faculty learning communities for web-enhanced learning / Anne H. Moore, Shelli B. Fowler, and Jennifer L.V. Sparrow -- The WEL project at the University of Genoa: effects on faculty attitudes and teaching practices / Manuela Repetto.